2019
DOI: 10.1016/j.parkreldis.2019.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of known pathogenic mutations in dominant PD genes: A Swedish multicenter study

Abstract: To determine the frequency of mutations known to cause autosomal dominant Parkinson disease (PD) in a series with more than 10% of Sweden's estimated number of PD patients. Methods: The Swedish Parkinson Disease Genetics Network was formed as a national multicenter consortium of clinical researchers who together have access to DNA from a total of 2,206 PD patients; 85.4% were from population-based studies. Samples were analyzed centrally for known pathogenic mutations in SNCA (duplications/triplications, p.Ala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…However, whole‐gene multiplications had been more frequently detected than the single‐nucleotide variants (SNVs). It has been reported that multiplications of SNCA are observed in around 0.05% of European PD patient populations . Other genes related to hereditary forms of PD have copy number variations (CNVs) demonstrating the role of loss of function .…”
mentioning
confidence: 99%
“…However, whole‐gene multiplications had been more frequently detected than the single‐nucleotide variants (SNVs). It has been reported that multiplications of SNCA are observed in around 0.05% of European PD patient populations . Other genes related to hereditary forms of PD have copy number variations (CNVs) demonstrating the role of loss of function .…”
mentioning
confidence: 99%
“…This variant was genotyped in our dataset but excluded during the pre-imputation QC due to low MAF (0.2%). Previous studies of PD cohorts in Sweden have shown that the prevalence of LRRK2 G2019S carriers is low in Sweden, 0.54% of screened 2206 PD patients were carriers [ 71 ]. It has been estimated that the G2019S mutation worldwide accounts for 4% of familial and 1% of idiopathic PD cases [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…The individuals that had been inaccurate imputed for the LRRK2 G2019S did not have a noticeable effect on the overall GRS in the cohort. Previous studies of PD cohorts in Sweden have shown that the prevalence of LRRK2 G2019S carriers is low in Sweden, 0.54% of screened 2206 PD patients were carriers (72). It has been estimated that the G2019S mutation accounts for 4% of familial and 1% of idiopathic PD cases (73).…”
Section: Discussionmentioning
confidence: 99%
“…This variant was genotyped in our dataset but excluded during the pre-imputation QC due to low MAF (0.2%). Previous studies of PD cohorts in Sweden have shown that the prevalence of LRRK2 G2019S carriers is low in Sweden, 0.54% of screened 2206 PD patients were carriers [72]. It has been estimated that the G2019S mutation worldwide accounts for 4% of familial and 1% of idiopathic PD cases [73].…”
Section: Discussionmentioning
confidence: 99%